An Uncommon Reason of Osteoporosis: Spondyloepiphyseal Dysplasia Congenita - Onur Elbasan; Pınar Şişman; Özen Öz Gül; Soner Cander; Canan Ersoy (Türk Osteoporoz Dergisi)
Skeletal dysplasia is a complex and rare disease group that presents with clinical and radiological findings that differ from classical metabolic bone diseases in which bone and cartilage tissue are affected together. Spondyloepiphyseal dysplasia conjenita with involvement of the spine and long bone epiphyses is seen with short stature and short body from birth. Although bone deformities such as shortness of neck and vertebrae, kyphosis, scoliosis, pectus carinatum, genu varum or valgum are frequent, association with osteopenia/osteoporosis has been rarely reported. Although spondyloepiphyseal dysplasia tarda and osteopenia are coexisting in the literature, there is no evidence of the association of spondyloepiphyseal dysplasia tarda and conjunctiva with osteoporosis. In our case report, we presented a patient who was applied to our center with short stature, diagnosed with osteoporosis and spondyloepiphyseal dysplasia congenita by detecting femur head aplasia in radiological imaging.